ANALISA PENGENDALIAN PERSEDIAAN SPAREPART MOTOR HONDA BEAT FI DENGAN METODE EOQ MENGGUNAKAN PERAMALAN PENJUALAN DI GRAHA KARYAAHASS XY - Erna Indriastiningsih; Semtandi Darmawan (Jurnal Ilmiah Dinamika Teknik, 2019)
The development of the automotive world in Indonesia has begun to advance and it is undeniable that the development has progressed very rapidly. With the developments that occur in the automotive world which is very influential in the industrial world in Indonesia also results in fierce competition. Forecasting is a calculation analysis technique that is carried out with a qualitative or quantitative approach to estimate future events using reference data from the past. Inventory control is the efforts made by a company including the decisions taken so that the need for materials for the needs of the production process can be optimally met with the smallest possible risk. This research was conducted at AHASS Graha KaryaXY. The data that has been used for research is bookkeeping data at Gudang for 6 months. Forecasting methods used are Exponential Smoothing and Linear Trend. Then control inventory with the EOQ method. The items studied were MPX1 Lt Engine Oil, Gardan Oil, VBELT, Brake Canvas, Brake Bulb. The results of the study, forecasting that is suitable for use is Linear Trend forecasting and using the POM-QM windwos 5 application with the results of MPX1 Lt Engine Oil is 20 bottles, 4 units of VBELT, 15 units of canvas brake, 4 units of axle oil, and 7 units of brake bulb. . And for the results of inventory control, MPX1 Engine Oil 23 days, VBELT 36 days, brake canvas 23 days, Gardan Oil 26 days, brake bulb once every 30 days. The results of forecasting are done, forecasting with the linear Trend method is very useful for AHASS Graha Karya XY and also inventory control using the EOQ method is very useful and feasible to apply.